Metaheuristics and Neutrosophic Sets for COVID-19 Detection: A review study - El-Shorbagy, M.A.; Nabwey, Hossam A.; İnç, Mustafa; Khater, Mostafa M. A. (American Scientific Publishing Group (ASPG), 2023)
The fast spread of COVID-19 has been a problem for several nations since February 2020. Computer-aided diagnostic technologies that are both effective and affordable are urgently needed to help ease the burden on healthcare systems. Researchers are delving further into the feasibility of using image analysis to detect COVID-19 in X-ray and CT-scan pictures of patients. In the past ten years, deep learning has surpassed every other method for classifying images. However, deep learning-based approaches' effectiveness is very sensitive to the design of the underlying deep neural network. In recent years, metaheuristics and neutrosophic sets have become more popular as a means of fine-tuning the structure of deep networks. Because of their adaptability, simplicity, and task dependence, metaheuristics have been extensively employed to tackle many difficult non-linear optimization problems. To correctly identify COVID-19 patients from their chest X-rays, the authors of this research made a review of a neurotrophic model and metaheuristics methods. © 2023, American Scientific Publishing Group (ASPG). All rights reserved.
Keywords: COVID-19; Metaheuristics; Neutrosophic Sets; X-ray